Longitudinal Cognitive Performance of Older Adults With ADHD Presenting to a Cognitive Neurology Clinic: A Case Series of Change Up to 21 Years - Callahan, Brandy L.; Shammi, Prathiba; Taylor, Rebecca; Ramakrishnan, Nayani; Black, Sandra E. (Frontiers in Aging Neuroscience, 2021)
Background: The neuropsychological features of older adults with ADHD are largely unknown. This retrospective chart review aims to elucidate their cognitive trajectories using a case series of six older adults with ADHD presenting with memory complaints to a cognitive neurology clinic, whom we argue are a particularly relevant group to study due to their potential to mimic neurodegenerative syndromes. Methods: Participants were included if they were age 40 or older at intake, had ADHD based on DSM-5 criteria, and had cognitive data collected prior to 2014 with follow-up at least 5 years later. Results: Five men and one woman were included (M = 54.3 years at intake) and had an average of 135.0 months of follow-up data available. Despite notable between- and within-subject variability, cognition generally improved or remained stable across visits. Two participants experienced notable memory decline, but a global consideration of their performance in other domains suggests these deficits may be frontally-mediated. Conclusion: In this small sample, cognition remained generally unchanged across 5-21 years. Isolated impairments likely reflect substantial intra-individual variability across time and measures.